Estimativa de medidas de tendência central: uma intervenção de ensino - Leite, Ana Paula Fernandes (2010)
The objective of this study was to investigate the contributions of an educational intervention, based on the significance and estimate measures of central tendency, from reading charts and tables. In order to achieve this purpose, we elaborated a character study of quasi-experimental design which included two distinct groups of a public school in the state of São Paulo. The first group, called the experimental group(GE), composed of 30 students who underwent a differentiated education based on the significance and estimate measures of central tendency, and the second group, called the control group (GC), composed of 27 students who had their classes routine. Were applied to both groups a pre-test to diagnose the level of prior knowledge of students involved, and a post-test after the teaching interventions, to diagnose the effects of these interventions. The theoretical framework of the study included the Theory of Conceptual Fields of Gérard Vergnaud (1982, 1990, 1993, 1996, 1997 and 1998). We also have some related studies by authors such as Batanero et al. (1997), Cazorla (2003), Echeveste et al. (2006), Araujo (2007), Meyen et al. (2007), Silva (2008), Pagan (2009) and Magina et al. (in press). The study aimed to answer the following question: "What contributions in terms of learning, a teaching intervention guided the significance and estimate measures of central tendency, brings high school students?". To this end, has become based on quantitative analysis of the results obtained in the statistical tests applied to two groups involved in the study. The analysis showed a significant gain with the teaching interventions in both GE and CG, as regards the seizure of the basic concepts of mean, mode and median, but a significantly higher performance was presented by students in the experimental group after intervention education. The result showed that the learning process of statistical content, guided by the significance and estimation proved to be effective on the cognitive gain by students on information presented as graphs and tables, and also how to gain strength in regarding knowledge of the statistical study, more specifically, Mean, Mode and Median